Estimation and correction of produced light from prompt gamma photons on luminescence imaging of water for proton therapy dosimetry. (12th February 2018) - Yabe, Takuya; Komori, Masataka; Toshito, Toshiyuki; Yamaguchi, Mitsutaka; Kawachi, Naoki; Yamamoto, Seiichi
Abstract: Although the luminescence images of water during proton-beam irradiation using a cooled charge-coupled device camera showed almost the same ranges of proton beams as those measured by an ionization chamber, the depth profiles showed lower Bragg peak intensities than those measured by an ionization chamber. In addition, a broad optical baseline signal was observed in depths that exceed the depth of the Bragg peak. We hypothesize that this broad baseline signal originates from the interaction of proton-induced prompt gamma photons with water. These prompt gamma photons interact with water to form high-energy Compton electrons, which may cause luminescence or Cherenkov emission from depths exceeding the location of the Bragg peak. To clarify this idea, we measured the luminescence images of water during the irradiations of protons in water with minimized parallax errors, and also simulated the produced light by the interactions of prompt gamma photons with water. We corrected the measured depth profiles of the luminescence images by subtracting the simulated distributions of the produced light by the interactions of prompt gamma photons in water. Corrections were also conducted using the estimated depth profiles of the light of the prompt gamma photons, as obtained from the off-beam areas of the luminescence images of water. With these corrections, we successfully obtained depth profiles that have almost identical distributions as the simulated dose distributions for protons. The percentage relative height of the Bragg peak with corrections to that of the simulation data increased to 94% from 80% without correction. Also, the percentage relative offset heights of the deeper part of the Bragg peak with corrections decreased to 0.2%–0.4% from 4% without correction. These results indicate that the luminescence imaging of water has potential for the dose distribution measurements for proton therapy dosimetry.